Toward the identification of Frankliniella species in Brazil (Thysanoptera, Thripidae) - Cavalleri, Adriano; Mound, Laurence A. (Zootaxa, 2012)
This paper provides an illustrated key to about 40 species of Frankliniella recorded from Brazil, together with notes abouteach species. Two new synonyms are established: Frankliniella longispinosa Moulton is a synonym of Frankliniellavaripes Moulton; Frankliniella rodeos Moulton is a synonym of Frankliniella gemina Bagnall, all described originallyfrom South America. One new species is described, Frankliniella graminis sp.n. is recorded from Poaceae in central andsoutheastern Brazil. Four species are newly recorded from Brazil: Frankliniella frumenti Moulton, Frankliniella gossypiana (Hood), Frankliniella musaeperda Hood and Frankliniella platensis De Santis.